THE IMPORTANCE OF MULTIMODAL TEACHING AND DIALOGIC TEACHING IN DEVELOPING SPEAKING COMPETENCE: THE IMPORTANCE OF MULTIMODAL TEACHING AND DIALOGIC TEACHING IN DEVELOPING SPEAKING COMPETENCE - Naubetbaeva, Nurzada (Журнал иностранных языков и лингвистики, 2025)
This article investigates the relevance of multimodal learning and dialogic teaching while teaching the speaking skills of A2-level students. The research findings confirm that if multimodal approaches and dialogic instructions are applied cumulatively, the speaking skills of students greatly enhance. The current study monitors how multimodal learning materials and dialogic approach assist in enhancing students’ language learning process as well as introducing communicative skill. The teaching of a foreign language in the contemporary education system with interactive and multimodal practices is becoming highly fashionable. The application of multimodal resources and dialogic methods is most critical for developing the oral competence of A2-level learners. The article presents an overview of multimodal teaching and dialogic methods’ effectiveness, connection, and practical usage.